2020
DOI: 10.3892/ol.2020.12013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of surgery and radiotherapy for survival of patients with clinically localized prostate cancer: A population‑based coarsened exact matching retrospective cohort study

Abstract: Radical prostatectomy and radiotherapy are currently the main treatment options for localized prostate cancer. However, no large cohort study comparing surgery and radiation has been performed in Japan or Asia. The objective of the current study was to compare the survival outcomes of patients with clinically localized prostate cancer and in elderly and young patients receiving surgery and radiotherapy. The survival outcomes of patients with localized prostate cancer (age at diagnosis ≤79 years, clinical T1-3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The selection process for the systematic review is shown in Figure 1 . With further assessment, according to inclusion and exclusion criteria, 27 studies were finally available for the systematic review and meta-analysis ( Table 1 ) [ 8–34 ].
Figure 1.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection process for the systematic review is shown in Figure 1 . With further assessment, according to inclusion and exclusion criteria, 27 studies were finally available for the systematic review and meta-analysis ( Table 1 ) [ 8–34 ].
Figure 1.
…”
Section: Resultsmentioning
confidence: 99%
“…EBRT alone or EBRT plus BT), 23 studies assessed OS and CSS. The quality assessment of the included studies according to the Newcastle-Ottawa scale is summarised in Table 2 [ 8–34 ]. In general, there were only two fair quality studies, while all 25 others had at least good quality ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most hypopharyngeal cancers are squamous cell carcinomas (HPSCC), which are less common than other head and neck malignancies and account for about 3–5% of squamous cell carcinomas of the head and neck. The incidence rate of cancer in the elderly increases with age and is higher in people over 65 ( 5 , 6 ). So as aging intensifies, the number of elderly with HPSCC is expected to rise in the future.…”
Section: Introductionmentioning
confidence: 99%